2017
DOI: 10.1055/s-0037-1598643
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the p16 and Ki-67 Biomarkers as Predictors of the Recurrence of Premalignant Cervical Cancer Lesions after LEEP Conization

Abstract: Objective To evaluate the expressions of biomarkers p16 and K i -67 in low-grade (LG) or high-grade (HG) lesions, and to relate them to risk factors and the recurrence of these lesions. Methods A retrospective case-control study of 86 patients with LG and HG lesions who underwent a loop electrosurgical excision procedure (LEEP) between 1999 and 2004. The control group was composed of 69 women with no recurrence, and the study group, of 17 patients with recurrence. All patients were followed-up over a two-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…In the study by Leite P. et al p16 positivity observed was 12.8% and 72.1% for LSIL and HSIL respectively. They also observed a significant relation between p16 positivity and recurrence with P-value of 0.018 (30). Comparative analysis of p16 and Ki67 with various recent studies and the present study is depicted in Table 4.…”
Section: Discussionsupporting
confidence: 76%
“…In the study by Leite P. et al p16 positivity observed was 12.8% and 72.1% for LSIL and HSIL respectively. They also observed a significant relation between p16 positivity and recurrence with P-value of 0.018 (30). Comparative analysis of p16 and Ki67 with various recent studies and the present study is depicted in Table 4.…”
Section: Discussionsupporting
confidence: 76%
“…However, after specifically analyzing HSIL with p16 and Ki-67 positivity and comparing the presence or absence of recurrence, the authors observed a significant difference (OR: 0.19, 95% CI 0.054–0.662, p = 0.010). The percentage of positive cells was higher in the nonrecurrence group, thus showing that the presence of these biomarkers could be useful in managing patients with HSIL, which differs from the findings of our study [26].…”
Section: Discussioncontrasting
confidence: 99%
“…A Brazilian study published in 2016 by Leite et al [26] examined the relationship between p16 and Ki-67 expression in LSIL and HSIL and the risk of recurrence after conization. They retrospectively assessed 86 patients divided into a control and a recurrence group (69 vs. 17) for 2 years after surgery, with a 6-month follow-up including cytology and colposcopy.…”
Section: Discussionmentioning
confidence: 99%
“…14 Several studies have shown increased sensitivity and specificity for cervical cancer screening using p16 staining in conjunction with other biomarkers, such as p16/Ki-67 15,16,[24][25][26] and Survivin, the inhibitor of apoptosis. 27 …”
Section: ■Discussionmentioning
confidence: 99%